مرشح فوق صوتي-ضوئي مُولّف من أجل الجيل القادم لشبكات النفاذ الضوئية - عفيف عزيز صقور (Tishreen University, 2019)
تعتبر شبكات النفاذ الضوئيـة التي تستخـدم تكنولوجيـا  التجميع بتقسـيم  طول الموجـة عالية الكثافة             (Dense Wavelength Division Multiplexing) DWDM حلولاً واعدة من أجل الجيل القادم لشبكات النفاذ الضوئية التي يمكن أن تزود المستثمر بعدة  Gbit/s  و بالتالي هناك طلب متزايد على العناصر الضوئية التي تستخدم هذه التكنولوجيا. يقدم البحث دراسة تصميمية متكاملة لعنصر ضوئي (يعتمد في تصميمه على استخدام تكنولوجيا التداخل فوق صوتي-ضوئي) بغية استخدامه كمرشح أو فارز أطوال موجة مجمعة في شبكات النفاذ الضوئية التي تستخدم تكنولوجيا DWDM .يكمن الهدف الرئيسي للبحث من خلال العمل على تحقيق تأدية عالية الدقة في تصميم المرشح و التي تتمثل في القدرة على التحكم و إدارة (32 قناة ) مجمعة ضمن ليف ضوئي أحادي النمط (Single Mode Fiber)  SMF و بفاصل طيفي 0.8 nm  .أنجزت الحسابات التصميمية ضمن النافذة الضوئية 1530-1565nm حيث تكون الضياعات داخل الليف الضوئي أحادي النمط لا تتجاوز .0.2dB/km The Optical Access Networks that use combining Technology (Dense Wavelength Division Multiplexing (DWDM)) are considered promising solutions for the net- generation of the optical access networks that can provide to the subscriber several Gbit/s; and consequently there is a growing demand for the optical components that use this technology. This research presents an integrated design study of optical elements (that depends in its design on the use of interaction acousto-optic technology) for the purpose of using it as a filter or separator of dense wavelength in optical access networks through DWDM technology. The main objective of the research is to reach a highly accurate performance in designing the Filter through the capability of control and management of 32 Channels combined in a Single Mode Fiber (SMF) with a spectral span of 0.8 nm. The Design calculations had been achieved into the optical window 1530-1565nm where the losses inside the Single Mode Fiber do not exceed 0.2 dB/Km.